The effect of price, promotion, and location on the purchase decision of subsidized KPR homes in PT. Sarana Persada Karina - Jefry Andi Tarigan; Nur' Aeni (Jurnal Mantik, 2023)
With the significant increase in urbanization and ongoing population growth, especially in big cities, the need for houses or places to live is increasing. The high demand for housing results in high housing prices. Because limited income can create obstacles for low-income people (MBR), especially people in South Cikarang City who cannot meet their basic needs. So the government offers solutions and opportunities for Low-Income Communities (MBR) through the subsidized Housing Loan (KPR) program to have decent housing at affordable prices. Home Ownership Credit (KPR) at PT. Sarana Persada Karina is currently in great demand by consumers. This is caused by several factors, namely price, promotion, and location on purchasing decisions. The method used is quantitative, the population in this study are consumers who have bought for the last 2 years with a sample of 110 respondents through instrument testing using validity and reliability tests using the Lisrel analysis tool version 8.80. Of all the tests that have been carried out, it has concluded that price, promotion and location have a positive and significant effect on purchasing decisions. Company PT. Sarana Persada Karina as the Developer of the Bumi Cikarang Asri Subsidized KPR Housing can be taken into consideration in order to improve purchasing decisions and increase sales and company objectives.